The Influence Of Work Culture And Employee Performance On service Quality At Bulog Office In NTB Region - Maryam, St; Arini, Gusti Ayu; Fahira, Sonia (Jurnal Konstanta, 2023)
This study aims to analyze the effect of work culture and employee performance on service quality at the NTB regional Bulog office. The type of research used is descriptive quantitative research. The population in this study were all employees of the NTB Regional Logistics Office and partners who collaborated with the NTB Regional Logistics Office. The number of samples used in this study were 51 employees and 51 partners. Data collection techniques used were interviews, documentation and distributing questionnaires containing questions about work culture, employee performance and service quality. The analytical tool used is multiple linear regression analysis. The results of data analysis show that; 1) Work culture has a positive and significant effect on the service quality of the NTB Regional Bulog Office, 2) Employee performance has a negative and significant effect on the service quality of the NTB Regional Bulog Office, 3) Work culture and employee performance together have a significant effect on the service quality of the Bulog Office West Nusa Tenggara Region.